Prediction of delamination crack growth in carbon/fiber epoxy composite laminates using non-local interface damage model. (20th June 2014) - Ijaz, Hassan; Asad, Muhammad; Gornet, Laurent; Alam, Syed Yasir
<x content-type="archive" xml:space="preserve">Abstract</x> The use of composite laminates is increasing in these days due to desired directional properties and low densities in comparison of metals. Delamination is a major source of failure in composite laminates where a crack like entity can initiate and propagate between different layers of composite laminates under given loading conditions. Damage mechanics based theories are employed to simulate the delamination phenomena between composite laminates. These damage models are inherently local and can cause the concentration of stresses around the crack tip. In the present study integral type non-local damage formulation is proposed to avoid the localization problem associated to damage formulation. A comprehensive study is carried out for the selection of different non-local variables. Finite element simulations based on proposed non-local damage models and classical local damage model are performed and results are compared with available experimental data for UD IMS/924 Carbon/fiber epoxy composite laminate.